Steady Natural Convection Heat and Mass Transfer Due to a Horizontal Line Source in the Presence Of Magnetic Field and Chemical Reaction - Rao Kanuri, Venkat; Dandu, Sridevi; Gottumukkala, Santhi; Rao Cheemalapati, Nagubabeswara (International Journal of Engineering and Technology, 2018)
Natural convective heat and mass transfer due to a horizontal line source at an adiabatic plate and plane plume flow are analyzed in the presence of magnetic field and chemical reaction. The case of an isothermal plate and a plate of varying temperature are also discussed. Certain qualitatively distinct behaviours of the transport parameters noticed are - for an adiabatic plate as well as an isothermal plate, the transport parameters have exhibited asymptotic behaviour with the Prandtl number and Schmidt number. For Plume flow centre line velocity has exhibited asymptotic behaviour with Prandtl number and Schmidt number. Transport parameters diminished but centre line velocity of the Plume increased with increasing magnetic field. Chemical reaction is seen to increase centre line velocity/Sherwood number and diminish skin friction/Nusselt number. Comparison of the results at an adiabatic plate with those at an isothermal plate and a plate of varying temperature is made.Â Â Â Â Â Â Â